Mass balance, metabolic disposition, and pharmacokinetics of a single oral dose of regorafenib in healthy human subjects - Gerisch, Michael; Hafner, Frank-Thorsten; Lang, Dieter; Radtke, Martin; Diefenbach, Konstanze; Cleton, Adriaan; Lettieri, John (Cancer chemotherapy and pharmacology, 2018)
Purpose To evaluate the mass balance, metabolic disposition, and pharmacokinetics of a single dose of regorafenib in healthy volunteers. In addition, in vitro metabolism of regorafenib in human hepatocytes was investigated. Methods Four healthy male subjects received one 120 mg oral dose of regorafenib containing approximately 100 µCi (3.7 MBq) [ 14 C]regorafenib. Plasma concentrations of parent drug were derived from HPLC–MS/MS analysis and total radioactivity from liquid scintillation counting (LSC). Radiocarbon analyses used HPLC with fraction collection followed by LSC for all urine samples, plasma, and fecal homogenate extracts. For the in vitro study, [ 14 C]regorafenib was incubated with human hepatocytes and analyzed using HPLC–LSC and HPLC–HRMS/MS. Results Regorafenib was the major component in plasma, while metabolite M-2 (pyridine N -oxide) was the most prominent metabolite. Metabolites M-5 (demethylated pyridine N -oxide) and M-7 ( N -glucuronide) were identified as minor plasma components. The mean concentration of total radioactivity in plasma/whole blood appeared to plateau at 1–4 h and again at 6–24 h post-dose. In total, 90.5% of administered radioactivity was recovered in the excreta within a collection interval of 12 days, most of which (71.2%) was eliminated in feces, while excretion via urine accounted for 19.3%. Regorafenib (47.2%) was the most prominent component in feces and was not excreted into urine. Excreted metabolites resulted from oxidative metabolism and glucuronidation. Conclusions Regorafenib was eliminated predominantly in feces as well as by hepatic biotransformation. The multiple biotransformation pathways of regorafenib decrease the risk of pharmacokinetic drug–drug interactions.